Signaling pathways and targeted therapeutic strategies for polycystic ovary syndrome - Wang, Kexin; Li, Yanhua (Frontiers in Endocrinology, 2023)
Polycystic ovary syndrome(PCOS) is the most common endocrine disorder among women of reproductive age. Despite promising strides have been made in the field of PCOS over the past decades, the clear etiologies of this syndrome are not fully elucidated. The prenatal factors, genetic variations, epigenetic mechanisms, unhealthy lifestyles and environmental toxins all contributed to the development of this intricate and highly heterogeneous metabolic, endocrine, reproductive and psychological disorder. Moreover, interactions between androgen excess, insulin resistance, disrupted hypothalamic-pituitary-ovary(HPO) axis and obesity only make a worse picture. In this review, we investigate and summarize the related molecular mechanisms underlying PCOS pathogenesis from the perspective of signaling pathways level, including PI3K/Akt, TGF-β/smads, Wnt/β-catenin and Hippo/YAP. Additionally, this review provides prospective therapies such as exosome therapy, gene therapy, and drugs from traditional Chinese medicine(TCM) and natural compounds. By targeting these aberrant pathways, these interventions primarily alleviate inflammation, insulin resistance, androgen excess and ovarian fibrosis which are typical symptoms of PCOS.As a whole, we hope that this paper will pave the way for a better understanding and management of PCOS in the future.